Programmed death‐1 blockade for multiple basal cell carcinomas: clearing the field systemically?. (17th September 2018) - Haug, V.; Schilling, B.
Abstract : Linked Article:  Moreira et al. Br J Dermatol 2018;179 :747–749 .